Sundanese Women in Politics: A Structural Analysis to Inform Educational Strategies for Gender Equality - Siti Komariah; Dini Asmiatul Amanah; Muhammad Retsa Rizaldi Mujayapura (Jurnal Cakrawala Pendidikan, 2025)
This study examines Sundanese women's participation in legislative institutions through a structuration theory approach to inform educational strategies for gender equality. The purpose of this study is to understand how structure-agent relation in Sundanese women to navigate and challenge socio-political barriers for equality. We used a qualitative phenomenological approach to collect data through in-depth interviews, observations, and document analysis, aided by NVivo 12 software for data reduction and coding. The research findings reveal a complex dynamic in which structural factors significantly shape political participation, but individual agency plays an important role in challenging and changing these structures and to inspire young women. This discussion contributes to the broader debate on gender, politics, and empowerment by education in the Indonesian context. To enhance women's political involvement, we require to make Sundanese political women as an agent to inspire young generation in school which support by pedagogy that build critical and democratic sphere